중환자실에서의 환자가족과 간호사 간 의사소통에 대한 중요도, 만족도 및 장애수준 비교 - 홍햇살; 장명옥; Hong, Haetsal; Jang, Myoungock (Chunghwanja Kanho Hakhoe chi, 2025)
Purpose : This study compared the levels of importance, satisfaction, and barriers of communication performance between family members and nurses in intensive care unit (ICU). Methods : The participants were 64 family members of patients admitted to an ICU and 66 nurses working in ICUs at a university hospital. The data were collected via structured questionnaires from December 27, 2023, to March 15, 2024, and were analyzed using descriptive statistics and t-tests to compare the responses of family members and nurses. Results : A higher importance of communication was conveyed by family members than by nurses (t=2.455, p=.015). Both groups recognized the importance of providing information related to the patient's condition and treatment. Satisfaction with communication was higher among families than nurses (t=5.172, p<.001). Both groups were satisfied with the items pertaining to the use of easy-to-understand language and the ability to answer their questions, but these were ranked differently. Nurses reported a higher barrier level than family members (t=-5.591, p<.001). Both groups agreed that nurses appearing busy or lacking the time to communicate were significant barriers. Conclusion : Family members of the patients in the ICU recognized the importance of communication and were satisfied with the communication with nurses. They preferred informative and friendly communication that focused on their needs. Therefore, interventions and educational programs for communication performance and environmental factors must be considered to optimize the quality of nursing services for family members in ICUs.